Antibacterial Test of Ruku-Ruku Leaf Extract (Ocimum tenuiflorum L.) Against the Growth of A. actinomycetemcomitans - Hanifah Ramadhanty; Aria Fransiska; Rahmi Khairani Aulia (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2025)
A. actinomycetemcomitans bacteria is the main pathogenic microorganism identified as the cause of aggressive periodontitis, with a prevalence of 90%. Periodontitis treatment is generally done mechanically by scaling root planning (SRP) and chemically by administering antibiotics as antibacterial agents. Specifically, ruku-ruku leaves contain several natural compounds with potential as antibacterials. This study, thus, aims to determine the potency of ruku-ruku leaf extract in inhibiting the growth of A. actinomycetemcomitans bacteria. This study employed a true experimental method in the form of a post-test-only control group design. Ruku-ruku leaf extract was prepared by a maceration method using 96% ethanol solvent and diluted with DMSO (Dimethyl Sulfoxide) to obtain concentrations of 10%, 20%, 40%, and 70%. The inhibition test was conducted using the Kirby-Bauer method, which utilized paper discs on Mueller Hinton Agar media. The zone of inhibition formed around the discs was measured. Data analysis was then performed using the One-Way ANOVA test, and the Post Hoc LSD (Least Significant Difference) test was continued. The results of this study revealed significant differences in inhibition from each treatment group. The concentration of 70% ruku-ruku leaf extract is more effective in inhibiting the growth of A. actinomycetemcomitans with an inhibition zone of 7.49 mm. Post Hoc LSD results uncovered p values of 0.001 and 0.003 (p<0.01). In conclusion, ruku-ruku leaf extract has potential antibacterial properties against the organization of A. actinomycetemcomitans.